2022
DOI: 10.3399/bjgp.2022.0104
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences of GP-led colon cancer survivorship care: a Dutch mixed-methods evaluation

Abstract: Background: Colon cancer survivorship care constitutes both follow-up and aftercare. General practitioner (GP) involvement may help to personalize care. Aim: To address patients’ experiences with GP- versus surgeon-led survivorship care. Design and setting: Stage I-III colon cancer patients were recruited from 8 Dutch hospitals and randomised to receive care by either the GP or surgeon. Method: A mixed-methods approach was used to compare GP- to surgeon-led care, consisting of questionnaire-based data (N=261) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, participants still expressed confusion about the follow‐up schedule, and roles and responsibilities of each provider when the model of care was not specialist‐led. Similar experiences have been reported in GP‐led models of follow‐up for CRC survivors 43 . While participants in the shared care arm of the SCORE trial received SCPs to facilitate communication, many could not recall using these and still found that their GPs were unsure of the study protocol, leading to distress that their care needs were not being met.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, participants still expressed confusion about the follow‐up schedule, and roles and responsibilities of each provider when the model of care was not specialist‐led. Similar experiences have been reported in GP‐led models of follow‐up for CRC survivors 43 . While participants in the shared care arm of the SCORE trial received SCPs to facilitate communication, many could not recall using these and still found that their GPs were unsure of the study protocol, leading to distress that their care needs were not being met.…”
Section: Discussionmentioning
confidence: 72%
“…Similar experiences have been reported in GP-led models of follow-up for CRC survivors. 43 While participants in the shared care arm of the SCORE trial received SCPs to facilitate communication, many could not recall using these and still found that their GPs were unsure of the study protocol, leading to distress that their care needs were not being met. Better communication tools are needed between hospital-based care providers, GPs, and patients as shared care models have been deemed less acceptable when survivors perceived poor communication between care providers.…”
Section: Communicationmentioning
confidence: 99%
“…There was high between-participant variation in how the responsibility of the different HCPs involved in PHFU was viewed. Unclarity about responsibility is also present in other forms of follow-up; previous studies have concluded that the quality of the perceived follow-up care suffered from this unclarity 20–22. Therefore, it is recommended that it is clearly defined for the patient which HCP has the main responsibility for the PHFU.…”
Section: Discussionmentioning
confidence: 99%
“…For the GP to take over completely, it will require additional time, compensation, and reorganization of the infrastructure ( 30 ). It will also require a clear understanding of the roles and responsibilities in which the patient and GP need to come to an agreement on who will take the lead in organizing follow-up ( 31 ).…”
Section: Discussionmentioning
confidence: 99%